IMPLEMENTATION OF E-SCM FOR CHIPS STOCK MANAGEMENT - Sri Wahyuni; Muhammad Ardiansyah Sembiring; Amalia (Jurnal Sistem Informasi, 2025)
Rumah Keripik Lely Tittiana is a business in the field of selling banana chips. Problems at Rumah Keripik Lely Tittiana include chips stock management experiencing shortages and excess stock due to delays in supplying raw materials by suppliers because ordering is still manual. Excessive stock causes product quality to decrease because it has an expiration period so that it can result in losses. The purpose of this research is to design an E-SCM application system for stock management of chips that experience shortages and excess stock at Lely Tittiana Chips House and implement a web-based E-SCM application using the PHP programming language and MySQL database at Lely Tittiana Chips House. E-SCM includes various parties ranging from suppliers, distributors, manufacturers, to customers with the aim of creating quality products. The research method used in this research is qualitative research method. The results of the implementation of this web-based E-SCM design make stock management more effective in overcoming the problems of excess and shortage of stock. This system helps in monitoring stock availability in real-time, so that decision making can be done more accurately.